The effect of own-firm and other-firm experience on foreign direct investment survival in the United States, 1987-92 - Shaver, J. Myles; Mitchell, Will; Yeung, Bernard (Strategic Management Journal, 1997)
We argue that foreign firms operating in a host country generate information spillovers that have potential value for later foreign direct investment. We test two predictions. First, we expect foreign direct investments by firms with experience in a host country to be more likely to survive than investments made by first-time entrants. Second, foreign direct investments will be more likely to survive the greater the foreign presence in the target industry at the time of investment, subject to two contingencies. The first contingency is that the relationship will be weak or nonexistent among firms with no experience in the host country, because these firms have difficulty evaluating and taking advantage of the information spillovers. The second contingency is that the presence of other foreign firms will not affect investment survival among firms that already have a presence in the target industry and undertake expansion. These firms already possess general information about the target industries and are unlikely to gain additional benefit from information spillovers. We find supportive evidence based on the survival to 1992 among 354 U.S. investments undertaken by foreign firms in manufacturing industries during 1987. © 1997 John Wiley & Sons, Ltd.